A CASE ASSESSMENT OF THE MECHANISMS INVOLVED IN HUMAN‐INDUCED LAND DEGRADATION IN NORTHEASTERN KUWAIT. (2nd March 2011) - AL‐Awadhi, J. M.
ABSTRACT Soil degradation and vegetation deterioration in contrasting areas (open desert versus protected desert) in the northeastern part of Kuwait were investigated, using field measurements, and laboratory methodologies. The average infiltration rate of compacted soils studied was found to be 52 per cent lower than that of the undisturbed soils we investigated. The bulk density of the compacted soils was 19 per cent higher than that of the non‐compacted soils. The average topsoil resistance of severely compacted soils was 13 per cent greater than that of undisturbed soils and is mainly due to overgrazing, and off‐road vehicle use. We found that the overall vegetation cover status of open areas investigated was approximately 70 per cent less than for the protected areas studied. As a consequence of soil compaction and vegetation deterioration, sand deflation processes, and sand movement prevail in open areas. The total average percentages of course grain sizes in unprotected soils and heavily disturbed soils by vehicles (off‐road) are 51 and 103 per cent greater, respectively. The annual rate of sand transport during the last 20 years, from the prevailing wind direction (NW) in the area has increased by 81 per cent. The delicate balance between soil and natural vegetation cover is easily disturbed by off‐road vehicle use associated with overgrazing and recreation activity. A restoration plan is needed in order to reduce land degradation and to allow natural vegetation recovery. Copyright © 2011 John Wiley & Sons, Ltd.